Peripartum Cardiomyopathy (Medicine Today, 2014)
Peripartum cardiomyopathy (PPCM) is an idiopathic cardiomyopathy that presents with heart failure secondary to left ventricular systolic dysfunction. Onset is from the last trimester of pregnancy to 5 months postpartum. Diagnosis in the last trimester is complicated by the fact that the early symptoms of this disorder may mimic the symptoms of normal pregnancy. However, it is essential for the practitioner dealing with such population to have a high degree of clinical suspicion for early diagnosis and management. Echocardiography is used to diagnose this entity and monitor the therapy. We present a case report of a 40-year-old woman who presented two days post-partum with respiratory distress and early echocardiography helped in diagnosing PPCM. The aim of this report is to make health professionals aware of the possibilities of PPCM in a woman with dyspnoea in the postpartum period. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17930 Medicine Today 2013 Vol.25(2): 96-98